Optimization of the esterification process of crude jatropha oil (CJO) containing high levels of free fatty acids: a Malaysian case study. Issue 6 (17th August 2020) - Farouk, Hazir; Zahraee, Seyed Mojib; Atabani, A.E.; Mohd Jaafar, Mohammad Nazri; Alhassan, Fatah H.
ABSTRACT: Biodiesel as an alternative fuel is one of the best choices among other sources due to its immense potential to reduce pollutant emissions when used in compression ignition engines. Malaysia is considered one of the top biodiesel-producing countries. The main crop for biodiesel production is currently palm oil. However, J atropha curcas has recently drawn the attention of the Malaysian government as an alternate species for producing high yields of oil. While an evaluation of biodiesel production, blending, engine performance and emissions characteristics of Malaysian-produced jatropha methyl ester has been made recently, few studies have optimized the esterification of the crude oil. This paper is the study of an optimization process for Malaysian CJO using an acid-catalyst pretreatment process to reduce the relatively high free fatty acid (FFA) percentages of crude jatropha oil to below 1% using design of experiments and response surface methodology, with the help of Minitab software. The main findings of the current investigation are that using the acid catalyst H2 SO4 at 0.225% (v/v), an MeOH-to-oil ratio of 12.29% (w/w) and a reaction time of 149.76 min are the optimum process parameters for the esterification reaction.